Q1: 20 points Q2: 20 points Q3: 30 points Q4: 30 points Total: 100 points
Question text is in black, solutions in blue.
DeMorgan's Laws say that for any propositions p and q, ¬(p ∧ q) is equivalent to ¬p ∨ ¬q and ¬(p ∨ q) is equivalent to ¬p ∧ ¬q.
The contrapositive of an implication p → q is the implication ¬q → ¬p. The contrapositive is equivalent to the original implication.
The Division Theorem says that if n is any integer and k is any positive integer, then there exist integers q and r such that n = qk + r and 0 ≤ r < k.
An odd integer n is one for which there exists an integer k such that n = 2k + 1.
The conclusion of an implication p → q is just the statement q.
You may use a truth table, apply Proof by Cases, or use other argument patterns that we have learned. (The truth table is probably simplest.)
Here's a case argument. Assume q. Then ¬p follows by Modus
Ponens on the first premise, and we have q ∧ ¬p which
contradicts the third
premise.
So this case is impossible. So consider the other case, and assume
¬q.
By the second premise, p must be true. But p ∧ ¬q is exactly
the
negation of p → q.
[(q --> not p) and (p or q) and not(q and not p)] --> not(p --> q)
0 1 1 0 0 0 0 0 0 1 0 0 1 0 1 0 0 1 0
1 1 1 0 1 0 1 1 0 0 1 1 1 0 1 0 0 1 1
0 1 0 1 1 1 1 0 1 1 0 0 0 1 1 1 1 0 0
1 0 0 1 0 1 1 1 0 1 1 0 0 1 1 0 1 1 1
By the Division Theorem, n is equal to 4q + r where q is an integer
and r is 0, 1, 2, or 3. Let A(n) be the predicate "n3
- n is divisible by 4" and let B(n) be the predicate "n is odd or
n is divisible by 4". We will prove that in each of the four
cases, A(n) ↔ B(n) is true.
We would like to prove by induction that for any positive integer n, this sequence obeys the closed formula an = 2n+1 - n - 2.
The statement P(n) is "an = 2n+1 - n - 2". The base case P(1) is "a1 = 21+1 - 1 - 2". The base case is true because a1 = 1 by the definition, and 22 - 1 - 2 = 4 - 1 - 2 = 1.
We assume P(n), which says that an = 2n+1 - n - 2. We want to prove P(n+1), which says that an+1 = 2(n+1)+1 - (n+1) - 2 = 2n+2 - n - 3.
We begin with an+1 and transform it into the desired expression. We first use the definition with k = n + 1 to say that an+1 = 2an + (n + 1). We then use the assumption to replace an, getting an+1 = 2(2n+1 - n - 2) + (n + 1) = 2n+2 - 2n - 4 + n + 1 = 2n+2 - n - 3. This proves that P(n) → P(n+1) and completes the induction.
Last modified 8 October 2014